In-situ electrochemical self-reconstruction of permeable Ni(OH)2/Pt hybrid for accelerating alkaline hydrogen evolution - Niankun Guo; Hui Xue; Jing Sun; Tianshan Song; Hongliang Dong; Zhonglong Zhao; Jiangwei Zhang; Qin Wang; Limin Wu (Next Materials, 2024)
Pt-based hybrid materials are demonstrated to be the most effective catalysts for alkaline hydrogen evolution reactions (HER) due to the synergy effect of heterogeneous interfaces. However, the heterogeneous interfaces are often constructed at the sacrifice of the electrochemical active surface area to cause relatively lower HER activity than expected. Herein, a permeable Ni(OH)2 layer and strained Pt atoms heterogeneous interface with enhanced electrocatalytic activity and minimal loss of active surface sites have been created by using an in-situ electrochemical self-reconstruction strategy. The permeable Ni(OH)2 layer promotes H2O dissociation without blocking proton contact with the active Pt sites. This unique design creates a favorable local acid-like environment that results in an ultra-high mass activity of 17.8 A mgPt−1 at an overpotential of 70 mV, which is 20.5 times superior to that of the commercial Pt/C catalyst and higher than those of the previously reported Pt-based catalysts. Meanwhile, the HER overpotential displays as low as 15 mV at 10 mA cm−2, showing superior HER efficiency and representing one of the optimal Pt-based HER catalysts in alkaline solution. In-situ Raman spectroscopy and DFT calculations prove that the interfacial synergistic interaction between permeable Ni(OH)2 layer and strained Pt atoms can significantly promote the H2O dissociation and the H2 formation. This electrochemical self-reconstruction method provides an effective and facile strategy for optimizing the electronic structure, electrocatalytic activity, and mass activity of active Pt atoms to develop efficient Pt-based heterostructure electrocatalysts.